2007
DOI: 10.1585/pfr.2.s1025
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Turbulence Imaging via Beam Emission Spectroscopy in the Core of the DIII-D Tokamak

Abstract: Beam Emission Spectroscopy (BES), a high-sensitivity, good spatial resolution imaging diagnostic system, has been deployed and recently upgraded and expanded at the DIII-D tokamak to better understand density fluctuations arising from plasma turbulence. The currently deployed system images density fluctuations over an approximately 5 × 7 cm region at the plasma mid-plane (radially scannable over 0.2 < r/a ≤ 1) with a 5 × 6 (radial × poloidal) grid of rectangular detection channels, with one microsecond time re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 27 publications
(30 reference statements)
6
48
0
3
Order By: Relevance
“…Furthermore, comparisons with E r from spectroscopy in W7-AS [40] and with E r from a Ball pen probe in ASDEX Upgrade [45] have also shown that v ph ≪ v E×B holds. In DIII-D, E r from beam emission spectroscopy and charge exchange recombination spectroscopy measurements also confirm the above statement [9].…”
Section: Figsupporting
confidence: 62%
See 2 more Smart Citations
“…Furthermore, comparisons with E r from spectroscopy in W7-AS [40] and with E r from a Ball pen probe in ASDEX Upgrade [45] have also shown that v ph ≪ v E×B holds. In DIII-D, E r from beam emission spectroscopy and charge exchange recombination spectroscopy measurements also confirm the above statement [9].…”
Section: Figsupporting
confidence: 62%
“…This is not observed here, so either the shear decorrelation mechanism does not play a central role or strongly non-isotropic structures are measured. However, anisotropic turbulence has been observed mainly at large scales (k ⊥ < 2 cm −1 ), while at smaller scales structures are isotropic [9,19,62,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,22,23 Figure 5 is an example of such an increase in density fluctuations measured with the beam emission spectroscopy (BES). 29 When the RMP-coil current is applied, the density pump-out is observed, but on a faster time-scale, there is an increase in the density fluctuations. The density fluctuations,ñ, at k h q s $ 0:3 À 0:5 initially increase by 50%, where k h is the wave number and q s is the ion sound gyroradius.…”
Section: Changes In Core Turbulencementioning
confidence: 97%
“…2D measurements of the turbulence in the R-Z plane were obtained over the radial range 0.9 < r/a ≤ 1 (extending slightly into the scrape-off-layer region) with the high-sensitivity beam emission spectroscopy (BES) diagnostic [11][12][13]. BES examines long-wavelength density fluctuations (k ⊥ < 3 cm -1 ) in the radialpoloidal plane.…”
Section: Turbulence Characteristics and Dynamicsmentioning
confidence: 99%